1990
DOI: 10.1017/s0021859600075249
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fill, forage palatability and alimentary behaviour in sheep

Abstract: S U M M A R YFive sheep were fitted with rumen cannulas and fed once daily ad libitum at 09.00 h with a low-quality mixed-grass hay or a good-quality lucerne hay. The effects of a second amount of the same hay or of the second hay distributed at the end of the large meal following the morning distribution, when rumen fill reaches its daily maximum, were investigated for feed intake, alimentary behaviour and rumen fill. The second distribution induced a true meal (200-400 g dry matter intake), except in the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 22 publications
2
20
0
2
Order By: Relevance
“…Despite this high proportion, sheep showed good adaptability, as they decreased their voluntary daily intake accordingly and stabilized it within 3 days. Sheep in treatments Lo/Lr and Go/Gr consumed an amount of hay such that they received similar total amounts as sheep orally fed lucerne or grass hay ad libitum with no time restriction (Baumont et al, 1990a). Our results are thus consistent with previous studies in which addition of 1 g of feed into the rumen lowered voluntary intake by about 0.9 g (Faverdin et al, 1995 for review).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite this high proportion, sheep showed good adaptability, as they decreased their voluntary daily intake accordingly and stabilized it within 3 days. Sheep in treatments Lo/Lr and Go/Gr consumed an amount of hay such that they received similar total amounts as sheep orally fed lucerne or grass hay ad libitum with no time restriction (Baumont et al, 1990a). Our results are thus consistent with previous studies in which addition of 1 g of feed into the rumen lowered voluntary intake by about 0.9 g (Faverdin et al, 1995 for review).…”
Section: Discussionsupporting
confidence: 89%
“…Palatability can be considered to reflect those characteristics of a food which invoked a sensory response in the animal (Greenhalgh and Reid, 1971;Baumont, 1996). For instance, the sensory motivation induced by offering a fresh meal of a palatable hay in satiated sheep could override satiety signals and induced a new meal (Baumont et al, 1990a). However, the food learning theory considers that palatability and post-ingestive consequences are interrelated , because ruminants can learn to associate the pre-ingestive characteristics of a food with its post-ingestive consequences and adjust their choices accordingly (Forbes and Provenza, 2000).…”
mentioning
confidence: 99%
“…It has been shown that satiated sheep ate a substantial meal after a second distribution of a sufficiently palatable hay; this meal was then associated with an increase in rumen fill of up to 10% of the daily maximum observed without this second distribution (Baumont et al, 1990b). The hedonic stimulation induced by the new distribution thus overrode the satiety signals due to rumen fill.…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 99%
“…The sensory response induced by a second distribution of fresh hay will override the satiety signals induced by the meal following the first distribution (Gatel, 1984). However, the size of the second meal depends on the relative palatability of the two hays distributed (Baumont et al, 1990). Sheep satiated with low-quality meadow hay will eat 400 g of lucerne hay (fig 1 however, Hedonic behaviour also competes with the effort that has to be expended to earn the reward.…”
Section: Hedonic Behaviourmentioning
confidence: 99%